Complexity within an oil palm monoculture: The effects of habitat variability and rainfall on adult dragonfly (Odonata) communities. (30th March 2020) - Luke, Sarah H.; Dwi Advento, Andreas; Dow, Rory A.; Aryawan, Anak Agung Ketut; Barclay, Holly; Eycott, Amy E.; Hinsch, Julie K.; Kurniawan, Candra; Naim, Mohammad; Mann, Darren J.; Pujianto,; Purnomo, Dedi; et al.
Abstract: Recent expansion of oil palm agriculture has resulted in loss of forest habitat and forest‐dependent species. However, large numbers of species—particularly insects—can persist within plantations. This study focuses on Odonata (dragonflies and damselflies): a charismatic indicator taxon and a potentially valuable pest control agent. We surveyed adult Odonata populations biannually over three years within an industrial oil palm plantation in Sumatra, Indonesia. We assessed the effects of rainfall (including an El Niño Southern Oscillation‐associated drought), the role of roadside ditches, and the importance of understory vegetation on Odonata populations. To assess the impacts of vegetation, we took advantage of a long‐term vegetation management experiment that is part of the Biodiversity and Ecosystem Function in Tropical Agriculture (BEFTA) Programme. We found 41 Odonata species, and communities varied between plantation core and roadside edge microhabitats, and between seasons. Abundance was significantly related to rainfall levels four months before surveys, probably indicating the importance of high water levels in roadside ditches for successful larval development. We found no significant effect of the BEFTA understory vegetation treatments on Odonata abundance, and only limited effects on community composition, suggesting that local understory vegetation structure plays a relatively unimportant role in determining communities. Our findings highlight that there are large numbers of Odonata species present within oil palm plantations and suggest that their abundance could potentially be increased by maintaining or establishing waterbodies. As Odonata are predators, this could bring pest control benefits, in addition to enhancing biodiversity within intensive agricultural landscapes. Abstract in Indonesian is available with online material. ABSTRAK: Perluasan perkebunan kelapa sawit dewasa ini telah mengurangi luasan habitat hutan dan spesies di dalamnya. Namun, sejumlah spesies khususnya serangga dapat hidup di areal perkebunan. Studi ini berfokus pada kelompok Odonata (capung dan capung jarum): takson karismatik yang berperan sebagai bioindikator dan memiliki potensi sebagai agen pengendali hayati. Pengamatan populasi imago Odonata dilakukan dua kali dalam setahun dengan durasi tiga tahun di areal perkebunan kelapa sawit di Sumatra, Indonesia. Terhadap populasi imago Odonata, kami telah menguji efek curah hujan (termasuk musim kering akibat El Niño Southern Oscillation / ENSO), pengaruh parit di tepi jalan, dan keberadaan tumbuhan liar. Pengujian pengaruh tumbuhan liar kami lakukan bersama dalam penelitian manajemen vegatasi tumbuhan di suatu program yang disebut Biodiversity and Ecosystem Function in Tropical Agriculture (BEFTA). Kami telah menjumpai 41 spesies Odonata dimana kami juga menemukan perbedaan komunitas tersebut antara bagian tengah blok kebun dan tepi jalan blok serta antara musim. Kelimpahan Odonata berhubungan erat dengan tingkat curah hujan secara signifikan dalam empat bulan sebelum survey, yang mengindikasikan tingginya genangan air parit yang mendukung perkembangan fase larva. Tidak ditemukan hubungan yang signifikan antara kelimpahan odonata dengan perlakuan vegetasi tumbuhan di areal BEFTA dan hanya terbatas di komposisi komunitasnya. Hal ini menandakan bahwa vegetasi tumbuhan liar memberikan efek yang relatif tidak cukup penting dalam menetukan komunitas odonata. Temuan kami mengindikasikan bahwa ada sejumlah besar spesies Odonata di perkebunan kelapa sawit dan secara potensial kelimpahannya dapat ditingkatkan dengan merawat atau membuat badan air berupa parit. Karena Odonata adalah predator yang dapat memberikan keuntungan pengendalian hayati sekaligus meningkatkan keragaman spesies di lanskap pertanian intensif.